Read, recite, and write cinquains - Macken, JoAnn Early, 1953- (St. Catharines, Ontario : Crabtree Publishing Company, 2015)
Introduces how to write poems in a five-line poetic form called a cinquain.
What is a cinquain -- Writing a sound cinquain -- Writing an animal cinquain -- Writing a dream cinquain -- Writing a story cinquain -- Writing a rhythmic cinquain -- Revising your cinquain -- Performing poem.
Includes bibliographical references (page 31) and index.
5.3
3-6
540L
Keywords: Poetry -- Authorship -- Juvenile literature; Cinquains -- Juvenile literature; Poetry -- Authorship; Cinquains